Conditional Effect of Environmental Degradation and Institutional Environment on Human Development in Developing Countries: Evidence from Method of the Moment-Quantile Regression with Fixed Effect - Kamalu, Kabiru; Binti Wan Ibrahim, Wan Hakimah (International Journal of Energy Economics and Policy, 2023)
The study examines the conditional effect of environmental degradation and institutional environment on the conditional distribution of human development, using the Method of the Moment Quantile Regression (MM-QR) technique with fixed effect, Fully Modified OLS (FMOLS) and Dynamic OLS (DOLS) estimators. The study uses strongly balanced data from 20 developing countries with the full data from 1996 to 2021. The findings confirmed heterogenous effects of environmental degradation and institutional environment on human development. The results reveals that lower environmental degradation promote human development across all levels of human development, but the effect higher in countries with low human development. The study shows that institutional environment has positive effect across all levels of human development, with higher effect in countries with low human development. The findings for the control variables show that financial development, population growth and FDI promote human development across all levels of human development. However, the strength of the coefficients also increases with higher quantiles. The results also confirmed unidirectional causality running from environmental degradation and institutional environment to human development, while bidirectional causality between financial development and human development. To promote human development, policymakers at developing countries should focus on climate action policies and building strong institutions.